Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1038/hr.2009.106
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of an angiotensin II receptor blocker in experimental model rats with hypertension and metabolic disorders

Abstract: Metabolic syndrome (MS) is an independent risk factor for chronic kidney diseases. As the renin-angiotensin system (RAS) is known to have a key role in renal damage, blockade of RAS may show renoprotective effects in MS. In this study, we investigated the renoprotective effects and mechanisms of action of an angiotensin receptor blocker (ARB) in spontaneously hypertensive (SHR/NDmcr-cp) rats as a model of MS. Male SHR/NDmcr-cp rats at 9 weeks of age were divided into three groups, each of which was treated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 44 publications
1
24
2
Order By: Relevance
“…Data from spontaneously hypertensive models suggest that hydralazine was unable to fully inhibit the development of fibrosis, but these findings can be explained by mechanisms independent of RAS activation. 41 In contrast to our findings in the present manuscript, there are examples in the literature of cases in which a reduction in blood pressure to normotensive levels did not abrogate organ damage, suggesting that fibrosis may be blood pressure independent under certain circumstances. 41,42 However, some of these studies had other important differences that should be taken into consideration, such as the presence of metabolic syndrome using genetically mutated mice, in which obesity, dietary supplementation, glucose intolerance and hyperinsulinemia likely contributed to end organ damage.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Data from spontaneously hypertensive models suggest that hydralazine was unable to fully inhibit the development of fibrosis, but these findings can be explained by mechanisms independent of RAS activation. 41 In contrast to our findings in the present manuscript, there are examples in the literature of cases in which a reduction in blood pressure to normotensive levels did not abrogate organ damage, suggesting that fibrosis may be blood pressure independent under certain circumstances. 41,42 However, some of these studies had other important differences that should be taken into consideration, such as the presence of metabolic syndrome using genetically mutated mice, in which obesity, dietary supplementation, glucose intolerance and hyperinsulinemia likely contributed to end organ damage.…”
Section: Discussioncontrasting
confidence: 55%
“…41 In contrast to our findings in the present manuscript, there are examples in the literature of cases in which a reduction in blood pressure to normotensive levels did not abrogate organ damage, suggesting that fibrosis may be blood pressure independent under certain circumstances. 41,42 However, some of these studies had other important differences that should be taken into consideration, such as the presence of metabolic syndrome using genetically mutated mice, in which obesity, dietary supplementation, glucose intolerance and hyperinsulinemia likely contributed to end organ damage. 41 The same can be said for a model combining aldosterone administration, uninephrectomy and a high salt diet, in which increased load on the remaining kidney likely contributed to organ damage.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Moreover, there is no evidence that a large amount of water can cure chronic kidney disease. Indeed, in the article we commented upon previously, Watanabe et al 3 did not provide the drinking and urinary volumes of the animals. However, in our personal experience, the use of ARBs does not increase the urinary volume in OLETF rats (type 2 diabetes model rats with accompanying hypertension).…”
mentioning
confidence: 99%
“…Watanabe et al also showed that olmesartan, an ARB, has protective effects on renal function resulting from the suppression of fibrosis in tubulo-interstitial tissue. 3 The increase in the renal plasma flow caused by ARBs is presumably sensitive to renal pathophysiological improvements rather than to excess water from the stimulated drinking behavior. As these rats showed 'hyperfiltration' before the use of ARBs, we concluded that the hemodynamic changes induced by the ARBs influenced renal function in the metabolic syndrome model.…”
mentioning
confidence: 99%